Acute Isolated Hyperbilirubinemia as a Presentation of Alcoholic Liver Disease: A Case Report and Literature Review. (12th February 2018) - Hossain, Muhammad Rajib; Pandey, Ramesh Kumar; Islam, Mohammad Faridul; Datar, Praveen; Gayam, Vijay; Puri, Pradeep; Malar, Thwin
Abstract : Isolated hyperbilirubinemia as a manifestation of alcoholic liver disease without significant liver abnormalities is seen very rarely. We report such a case where a patient with chronic alcoholism presented to the ER with acute jaundice with bilirubin of 24.8 mg/dl, predominantly conjugated in nature along with mild elevation of AST (76 IU/L). There were no other abnormalities of the liver function. The patient underwent extensive laboratory and imaging tests that excluded extrahepatic cholestasis, viral and autoimmune hepatitis, ischemic hepatitis, and so forth. Liver biopsy excluded hemochromatosis, dysplasia, or malignancy and other differentials. Bilirubin gradually trended down to 7.3 mg/dl when alcohol consumption was stopped.